2013
DOI: 10.1016/j.shaw.2013.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive Study of Occupational Accidents and their Causes among Electricity Distribution Company Workers at an Eight-year Period in Iran

Abstract: BackgroundOccupational accidents are unplanned events that cause damage. The socio-economic impacts and human costs of accidents are tremendous around the world. Many fatalities happen every year in workplaces such as electricity distribution companies. Some electrical injuries are electrocution, electric shock, and burns. This study was conducted in an electricity distribution company (with rotational 12-hour shift work) in Iran during an 8-year period to survey descriptive factors of injuries.MethodsVariable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 25 publications
5
43
0
4
Order By: Relevance
“…Unlike with the current study [32] on the Tanzanian construction industry found out that less than half of the workers had completed primary education. Furthermore, the study conducted by Rahmani et al [26] on Iran's construction industry also noted that most of the participants 46.2% had diploma qualifications.…”
Section: Participant's Socio-demographic Characteristicsmentioning
confidence: 93%
See 2 more Smart Citations
“…Unlike with the current study [32] on the Tanzanian construction industry found out that less than half of the workers had completed primary education. Furthermore, the study conducted by Rahmani et al [26] on Iran's construction industry also noted that most of the participants 46.2% had diploma qualifications.…”
Section: Participant's Socio-demographic Characteristicsmentioning
confidence: 93%
“…In addition, it was revealed by the study conducted in Taiwan, that 38% of workers in the construction industry do not use PPE correctly [25] which is a sign of ignorance or unsafe acts or lack of knowledge. Lack of PPE use was also reported as contributing to 54.5% accidents in the construction industry [26] as some employers do not provide PPE to their workers, while some work-Open Journal of Safety Science and Technology ers prefer not to use them even if they have been supplied by their employers [27]. Therefore, it is the employer's responsibilities to ensure that workers are supervised on wearing safety tools when performing jobs at construction sites, even though workers should be informed to take responsibility for their own health and safety especially by imposing punishment if they are not adhering to safety rules [28].…”
Section: E M Nghitanwa L Zungu Open Journal Of Safety Science Andmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of behavioral psychology, behavior is a function of environment in which it occurs. Unsafe work behavior is accordingly the result of (1) the physical environment, (2) the social environment, and (3) the workers' experience (McSween, 2003 ;Rahmani et al, 2013). Relationship between workload and job satisfaction is proven is some study (Khandan & Maghsoudipour, 2012).…”
Section: Ergonomic Behaviormentioning
confidence: 99%
“…Preventing occupational accidents is an important task of human resource management. Multifactorial interventions can be effective in decreasing occupational accidents [9]. Process analysis and improvement methods can be easily implemented for OHSbased improvement attempts.…”
Section: Introductionmentioning
confidence: 99%